Does Labor Market Tightness Affect Ethnic Discrimination in Hiring? - Magnus Carlsson; Luca Fumarco; Dan-Olof Rooth (Institute of Labor Economics (IZA), 2018)
Several studies using observational data suggest that ethnic discrimination increases in downturns of the economy. We investigate whether ethnic discrimination depends on labor market tightness using data from correspondence studies. We utilize three correspondence studies of the Swedish labor market and two different measures of labor market tightness. These two measures produce qualitatively similar results, and, opposite to the observational studies, suggests that ethnic discrimination in hiring decreases in downturns of the economy.
Keywords: C93; J15; J21; J71; 330; hiring discrimination; ethnic discrimination; labor market tightness; the business cycle; correspondence studies; field experiments; ranking models; screening models